Comparing Laparoscopic Sacrocolpopexy with Vaginal Sacrospinous Ligament Fixation in the Treatment of Vaginal Apical Prolapse; the First Randomized Clinical Trial: A pilot study - Daneshpajooh, Azar; Pakmanesh, Hamid; Sohbati, Samira; Mirzaei, Mahboubeh; Zemanati, Ehsan; Dehesh, Tania (Urology Journal, 2022)
Purpose: To compare two methods of laparoscopic sacrocolpopexy (LSCP) and sacrospinous ligament fixation (SSLF) in terms of efficacy and safety in the treatment of vaginal apical prolapse. Materials and Methods: This prospective, randomized controlled clinical trial was conducted on 32 patients with symptomatic vaginal apical prolapse, referred to the female urology clinic of Kerman University, Iran, during 2018-2019. The patients were re-examined at 12 months after surgery. Objective success was recorded using Pelvic Organ Prolapse Quantification (POP-Q) classification as primary outcome. The subjective success of the methods was determined by the quality-of-life parameters, based on Pelvic Floor Impact Questionnaire (PFIQ-7), Pelvic Floor Distress Inventory (PFDI-20), and Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) scores as secondary outcomes. Moreover, complications were recorded in both groups. Results: The amount of intraoperative bleeding was significantly higher in the SSLF group, compared to the LSCP group (P = 0.01). Persistent pain was observed in two (12%) patients in the LSCP group and five (31%) patients in the SSLF group (P = 0.2). The decrease in the total PFIQ-7 score was in favor of the LSCP group but not statistically significant (p = 0.06). The LSCP group showed bigger improvement in vaginal (p = 0.04) and bowel (p = 0.03) scores. The results of the PISQ-12 and PFDI-20 questionnaires as well as POP-Q examination were not different in two groups. Conclusion: Although the surgical methods of LSCP and SSLF can be equally effective in the treatment of apical prolapse, LSCP appears to be superior to SSLF regarding less bleeding.